2019
DOI: 10.3390/mca24010032
|View full text |Cite
|
Sign up to set email alerts
|

Global Sensitivity Analysis to Study the Impacts of Bed-Nets, Drug Treatment, and Their Efficacies on a Two-Strain Malaria Model

Abstract: Malaria is a deadly infectious disease, which is transmitted to humans via the bites of infected female mosquitoes. Antimalarial drug resistance has been identified as one of the characteristics of malaria that complicates control efforts. Typically, the use of insecticide-treated bed-nets (ITNs) and drug treatment are some of the recommended control strategies against malaria. Here, the use of ITNs, drug treatment, and their efficacies and evolution of antimalarial drug resistance are considered to be the maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 66 publications
1
6
0
Order By: Relevance
“…This means that malaria incidence would increase by 0.960 percent as income inequality rises by one percent. This result is consistent with a recent study [ 39 ] where it is contended that the long-term effects of inequality become apparent when a high growth rate for vulnerable people with low income is observed. This indicates that rising economic disparity would increase the number of persons who find it difficult to afford both personal protection against malaria and its treatment because this category includes the lowest-income earners.…”
Section: Ardl Model Estimation Resultssupporting
confidence: 93%
“…This means that malaria incidence would increase by 0.960 percent as income inequality rises by one percent. This result is consistent with a recent study [ 39 ] where it is contended that the long-term effects of inequality become apparent when a high growth rate for vulnerable people with low income is observed. This indicates that rising economic disparity would increase the number of persons who find it difficult to afford both personal protection against malaria and its treatment because this category includes the lowest-income earners.…”
Section: Ardl Model Estimation Resultssupporting
confidence: 93%
“…A study has showed that even with bednets usage by the entire population, the reduction of malaria transmission would be constrained to a certain minimum level. This is due to the fact that bednets are typically used during the night [ 43 ], and studies have documented instances of early mosquito bites occurring when people are outdoors [ 42 , 44 ]. Interventions’ effects might be affected by many factors, such as human behaviour, mosquito behaviour, pyrethroid vector resistance or the physical integrity of bednets.…”
Section: Discussionmentioning
confidence: 99%
“…The history of mathematical epidemiologic models date as far back as Bernouilli [16] , [17] , [18] . Mathematical models of a two-strain disease are numerous in the literature [19] : malaria [20] , influenza [21] , [22] , SARS-CoV-2 [23] , dengue [24] , disease with age structure and super-infection [25] , influenza with a single vaccination [26] , [27] to cite but a few and the references therein.…”
Section: Introductionmentioning
confidence: 99%